Polymerase Chain Reaction (PCR): A Short Review (Anwer Khan Modern Medical College Journal, 2013)
Diagnosis of disease now a days is mostly laboratory dependent. Due to recent advances in medical science and molecular biology, most of the diagnosis of uncommon, complicated, unusual presentation of disease has left the option of molecular diagnosis as the number one diagnostic modalities. Many molecular techniques are now being widely used throughout the  world including PCR, flow cytometry, tissue microarray, different blots, and genetic diagnosis. Among these PCR is the most widely accepted, commonly used diagnostic modalities with very high specificity and sensitivity for correct diagnosis. We have reviewed the principle, application, advantages and disadvantages of PCR in laboratory diagnosis of disease. DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13682 AKMMC J 2013: 4(1): 30-36